FENOMENA TIDAK MEMILIH (NON-VOTERS) DAN ALASAN PEMILIH TIDAK MENGGUNAKAN HAK PILIHNYA PADA PEMILUKADA BUPATI DAN WAKIL BUPATI TAHUN 2010 DI KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Rusdi Effendi (Universitas Lambung Mangkurat, 2012)
Elections in a democracy is one of the fundamental pillars of a process of accumulation willingness of the people. Elections are also a democratic procedure to elect the leader. Elections are the mechanism of power transformation (succession) is the most secure, when compared with other methods. Elections can be said is the fundamental pillar of a democracy. To select regional head and deputy regional head at the district level, was held Election Regional Head and Deputy Head of Region (Election) to select candidates for the Regent and Vice Regent as leaders at the local level. From the previous times elections, the elections and the General Election in Tanah Bumbu allegedly contained the presence of voters who did not vote (non-voters) tend to increase, because of that study was conducted to reveal a phenomenon not choose (non-voters) and Reasons the Voters are not voting in the general elections local Head and Deputy Head (Election) in the year 2010 in the District of Tanah Bumbu, South Kalimantan.Keywords: Phenomenon, not chosen (non-voters), Reason Voters, Election.